ASSESSMENT OF PSYCHOLOGICAL TEST RESULTS OF FRESHMEN EDUCATION STUDENTS - Aure, Ma. Rachel Kim L; Casinillo, Leomarich F (IJIET (International Journal of Indonesian Education and Teaching), 2021)
Psychological testing in schools is a beneficial activity that helps a student achieve their goals and helps diagnosed social, cognitive, or behavioral problems. This study aimed to assess the psychological test results of education students in a Philippine state university. The study utilized secondary data from 443 education students at the university. Descriptive measures and multiple regression models were employed in evaluating the data and determining the influencing factor of psychological test results, respectively. Results revealed that the selected demographic variables as gender, degree program, type of high school, and over- all grade point average have no significant association with the psychological test results of education students. Furthermore, this study has documented the robust and positive evidence that Mathematics and English grade point average contributed to the psychological test scores of the students. The results go to infer that students with a good background in Mathematics and English subjects in high school have a good foundation in analytical and logical thinking during college.